Kemampuan Pemecahan Masalah Matematis Siswa pada Pembelajaran Kooperatif Tipe Think Pair Share (TPS) Berbantuan Blooket Ditinjau dari Minat Belajar Siswa - Figur Pradano, Maulana; Mulyono, Mulyono (Paedagogie, 2025)
The purpose of this experimental study was to determine the effectiveness of mathematical problem-solving skills (KPM) in cooperative learning using Think Pair Share (TPS) with the aid of a blackboard and to describe mathematical problem-solving skills in terms of student learning interest in learning using the blackboard. The method used was a mixed-method sequential explanatory design. The research sample consisted of one experimental class and one control class, each with 34 students randomly selected from all eighth-grade students at SMP N 1 Banjarnegara in the 2024/2025 academic year. The research instruments were a mathematical problem-solving ability test and an interest questionnaire. A one-sample t-test was used to analyze the 75% completeness. The difference in means was analyzed using an independent sample t-test and a two-proportion difference test with a probability value (1 - ½ ∝) to compare the effectiveness of the TPS-based blackboard-based KPM with the control group. Interest in KPM was described using linear regression and triangulation. The results of the study indicate that mathematical problem-solving ability in the Think Pair Share (TPS) Cooperative Learning Assisted by Blooket achieved 75% classical mastery with a class average of 85.44. The independent sample t-test of 2.966 was greater than the t-table with a significance of 0.004 below 0.025 and the classical mastery proportion of 2.505 was above normal, meaning that the KPM in the TPS type in the form of a Blooket was effective. F count 1.353 < F table 2.278 and significance 0.266 > 0.05 there is a relationship between student learning interest and Mathematical KPM using linear regression. By comparing interest in KPM in Blooket-assisted TPS type learning, where the interest scale for high criteria is 73 to 100, interest for medium criteria is 47 to 73 and interest for low criteria is 20 to 47, while using 4 Mathematical KPM indicators according to NCTM (2000) is able to produce interest in the high category of 97% and moderate interest of 3%. High category interest subjects are able to fulfill indicators (1), (2), (3), (4). Subjects of interest in the medium category are able to fulfill indicators (1), (2), (3), and are not yet able to fulfill indicator (4). There are no representative subjects in the low category of interest.